EFFECT OF SHEAR WALL ON BUILDING STRUCTURE RESPONS - Wendy Boy; Rafki Imani; Romi Jaya (Construction and Material Journal, 2019)
Cibubur is an area in the earthquake zone. The intensity of the earthquake increases every year; therefore, this must be watched out because it will cause the existing buildings to be short-lived. To deal with these problems, various ways are carried out such as making building stiffeners in the form of a shear wall. This study aims to determine the position of an efficient shear wall. The method for analyzing this shear wall was first modeled. The shear wall laying model was divided into four. With the four models, it would be able to choose which model was efficient to reduce the earthquake that occured. Analysis used ETABS software on each model, and output in the form of drift and base shear. These results will become a reference for effective model selection. Based on the results of drift and base shear in the direction of X and Y direction, of the four shear wall placement models of Tower B Trans Park and Trans Studio Cibubur, the most efficient in resisting earthquake loads is the original model. With a save value of direction X is 926.62 mm, and Y is 931.22 mm. The value of the base shear on direction X is 4691.71 tons, and Y is 4736.57 tons.Keywords: Base shear, Drift, Earthquake; Shear wall